A case of lipomembranous panniculitis with a dramatic response to the treatment of venous insufficiency - Didem Mullaaziz; Aslı Kaptanoğlu; Emel Erdal Çalıkoğlu; Hanife Özkayalar (PAGEPress Publications, 2018)
Lipomembranous panniculitis (LP) is a peculiar type of fat necrosis and is reported with various clinical conditions, mostly with peripheral vascular diseases. Here, a case of a 57-year-old woman with a painful erythematous swelling of the right leg in association with venous insufficiency has been reported. Although LP is frequently associated with venous insufficiency, to the best of our knowledge, this is the first report on the beneficial effect of venous insufficiency treatment in LP.